1979
DOI: 10.1159/000149039
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies in Human Sera Reacting with an Insect Pathogenic Virus

Abstract: Precipitating antibodies to an insect pathogenic RNA virus of Darna trima from East Malaysia have been found in a small percentage of human sera from several different groups of persons in West Malaysia and the United Kingdom. No associated illness was identified. The results suggest that an antigenically related virus or viruses are present in the environment that may be associated with symptomless or inapparent infections in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…While the applications were undoubtedly successful there has been some reluctance to consider further field use of this type of virus. There are no viruses identified in mammals which resemble the viruses of this family, but MacCallum et al (1979) have reported the presence of precipitating antibodies to the D. trima virus (originally isolated in East Malaysia) in a small number of human sera from individuals in West Malaysia and the United Kingdom. There are at least three possible explanations of these serological interactions.…”
Section: Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the applications were undoubtedly successful there has been some reluctance to consider further field use of this type of virus. There are no viruses identified in mammals which resemble the viruses of this family, but MacCallum et al (1979) have reported the presence of precipitating antibodies to the D. trima virus (originally isolated in East Malaysia) in a small number of human sera from individuals in West Malaysia and the United Kingdom. There are at least three possible explanations of these serological interactions.…”
Section: Replicationmentioning
confidence: 99%
“…Much of the research in insect virology has been directed towards the use of viruses as field control agents for pest species, but it is unlikely that small RNA viruses will be used extensively for this purpose until more is known about their molecular biology, pathology and host range. A major problem regarding their potential use as insect control agents is created by several reported interactions between small RNA viruses of insects and antibodies in mammalian sera (Longworth et al, 1973b;MacCallum et al, 1979;Scotti & Longworth, 1980;Moore et al, 1981b). It is likely that inadequate monitoring of baculovirus preparations used in field control of pest insects has led to the accidental spread of small RNA viruses (Hess et al, 1977(Hess et al, , 1978.…”
Section: Introductionmentioning
confidence: 99%
“…In a very broad study, MAcCnI~I,tr3~ et al (57) found reactions between the sera of mammMs including man and viruses of the Nudaurelia ~ and enterovirus groups (unpublished information on the reactions with CrPV and the sera from many animals). SCOTTI and LONGWORTtI (113) found reactions against CrPV in cattle in New Zealand and observed that the sera could neutralize CrPV in tissue culture in addition to causing immunoprecipitation.…”
Section: Serologymentioning
confidence: 99%